Developing Variety of Handball Attacking Strategies Training for Malang Handball Athletes - Hadi, Antonius Prasetyo; Mustofa, Habibullah; Lufthansa, Luthfie (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
The research aims to develop learning media products as a reference book to improve handball athletes in Malang city's attack strategy techniques. The method used in this research is the development method (Research and Development) from Brog and Gall. In this development of the research, a reference book was produced on variations of an attack training strategy for Handball athletes in Malang. The research results of the analysis data from the Analysis Expert of handball training with a value of 4,03 on a scale of 1 to 5 with a good predicate, the results of validation by the Expert of media with a value of 4,22 on a scale of 1to 5 with a good prediction. The research results from the first phase trial showed a small group with a percentage of 7,43%, the research results in the second phase trial with a percentage of 78,57%, and in the field trial, a percentage of 83,33% was obtained. Based on the results of management data, the developed book product was declared fit for use as a learning media for attack training strategy of variation for handball athletes in the city of Malang.